Finite Element Analysis of Three Dimensional Force System from Beta Titanium and Steel Preactivated Retraction Springs - Sh Alavi; A Shirvani (Isfahan University of Medical Sciences, 2009)
Introduction: The aim of this study was to investigate the effects and interactions of first- andsecond- order preactivation bends on three dimensional force system of steel and beta titaniumcanine retraction springs.Method and materials: In a non- linear finite element analysis, three retraction springs including,vertical loop, vertical helical loop and T- loop were studied. All combinations of first-order bend(0, 20, 40 and 60 degrees), second-order bend (0, 20 and 40 degrees) and wire material (stainlesssteel, beta titanium) were applied to each design. All appliances activated incrementaly to reachelastic limit in 0.05 mm steps. Moment/ force ratios (in occlusal and sagital plan) and load/deflection rate of appliances were measured using ABAQUS, V6.8 and CATIA, V5.13 softwares.Results: It was found that the second-order bend can somewhat reduce moment/ force ratio inocclusal plan but first order bend have no effect on moment/ force ratio in sagital plan. Theaddition of helix into the vertical loop reduces load deflection rate of spring but did little to alterthe moment/ force ratios of spring.Conclusion: First and second-order preactivation of retraction springs produce the desired effects,without significant interfering with each other. Helices added to the vertical loop may improvesome mechanical characteristics of retraction springs.Key words: Orthodontic Appliance Design, Orthodontic Wires, Finite Element Analysis, StainlessSteel, Beta Titanium, Tooth Movement